Scientific and technical employment, 1990-2005 - Braddock, Douglas J. [Verfasser] (My University, 1992)
"In general, the analysis presented in this article has indicated that, for the period 1990-2005, supply and demand could approximate the levels existing in the late 1980's assuming reasonable adjustments to supply under the high or low growth alternatives. However, tha analysis also shows that supply-and-demand imbalances are possible under each of the alternatives advanced. It should be emphasized that the analysis presented covers the very broad area of natural science and engineering. Individual science and engineering occupations are not examined, and they could be affected differently. Nor is the special case of potential shortages of Ph.D.'s examined. Such issues cannot be addressed currently with available data. The analysis presented also does not address potential college faculty shortages, an area that has received much attention. Furthermore, the analysis does not address questions about the quality of new science and engineering graduates or the decline in the availability of technically trained workers for a variety of nonprofessional occupations, from mechanics to health technicians." (author's abstract) ((en)) Beschäftigungsprojektionen zu Wissenschaftlern, Ingenieuren und Technikern zeigen Wachstumsspielräume von 9% bis 59% über die Periode von 1990-2005 auf. Dabei wird deutlich, dass sich Angebot und Nachfrage dem Niveau, welches Ende der 80er Jahre bestand, nähern könnten. Die Analyse zeigt, dass Angebots- und Nachfrageschwankungen unter den betrachteten Alternativen möglich sind, wenn die Wahl der Hochschulstudenten Wissenschafts- und Ingenieurwesen zu studieren, nicht die Arbeitsmarktbedingungen wiederspiegelt - das heisst, wenn hohe Nachfrage und niedriges Angebot oder geringe Nachfrage und hohes Angebot ausschlaggebend sein sollten. (IAB)
Beschäftigung von Wissenschaftlern und Ingenieuren, 1990-2005
Keywords: G 1.2.1 Grund- & Strukturdaten des Arbeitsmarktes; T 3 Forschungsmethoden; G 1.1 Soziostrukturelle & Ökonomische Entwicklungen; G 1.2 Arbeitsmarkt; S 6.3.1 Ingenieurberufe, Chemiker, Physiker, Mathematiker; S 6.4.6.2 Wissenschaftliche Berufe; Beschäftigungsentwicklung; Prognose; Ingenieur; Naturwissenschaftler; Arbeitskräfteangebot; Arbeitskräftenachfrage; Berufsproblem; Quantitative Angaben